2005
DOI: 10.1103/physreve.72.010903
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive features of the biological catch bond in the jump-ramp force regime predicted by the two-pathway model

Abstract: The receptor-ligand unbinding in the biological catch bond is analyzed within a simple model that comprises a single bound state and two unbinding pathways. This model is investigated in detail for the jump-ramp force regime, where the pulling force quickly jumps to a finite value and then is ramped linearly with time. Two qualitative criteria are identified that distinguish the catch bond from the slip bond. First, the rupture force probability density of the catch-bond exhibits a maximum-minimum pair, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 18 publications
3
61
0
Order By: Relevance
“…Here, we define as the ratio of maximum lifetime t max ϭ t( f cr ) to the minimum lifetime t min below the critical force. We favor this definition of the efficiency as opposed to t( f cr )/t( f ϭ 0) (27) because it excludes the assumption that bond lifetime decreases monotonically as force approaches zero. Indeed, the general 2-state model predicts the intriguing possibility of 2-fold ''slipcatch-slip'' transitions if the bent dissociation pathway displays a strong force dependence.…”
Section: Selectin-ligand Kineticsmentioning
confidence: 99%
“…Here, we define as the ratio of maximum lifetime t max ϭ t( f cr ) to the minimum lifetime t min below the critical force. We favor this definition of the efficiency as opposed to t( f cr )/t( f ϭ 0) (27) because it excludes the assumption that bond lifetime decreases monotonically as force approaches zero. Indeed, the general 2-state model predicts the intriguing possibility of 2-fold ''slipcatch-slip'' transitions if the bent dissociation pathway displays a strong force dependence.…”
Section: Selectin-ligand Kineticsmentioning
confidence: 99%
“…Bartolo et al (2002) questioned the single path assumption in a theoretical study. Interestingly, the interest of the point raised by these authors was soon supported by the experimental demonstration of the reality of catch bonds (Thomas et al, 2002 ;Marshall et al, 2003) whose rupture behaviour was found consistent with the hypothesis that there indeed were two dissociation pathways with different sensitivity to external forces Pereverzev et al, 2005). Note that the reality of multiple pathways is also supported by molecular dynamics simulation (Martinez et al, 2005).…”
Section: Extracting Barrier Position From Force Spectroscopy Datamentioning
confidence: 67%
“…Indeed, antibodies are multivalent and it has long been known that the efficiency (often called "avidity") of antibody samples is often related to their capacity to form multivalent bonds. It is therefore of interest to mention recent experimental studies using dynamic force spectroscopy to analyze parallel bonds between antibodies and antigens such as mucin (Sulchek et al, 2005) or chelated uranyl (Odorico et al, 2007 (Chen et al, 2001 ;Rinko et al, 2004 ;Perret et al, 2004) and theoretical (Pereverzev et al, 2005 ;Dudko et al, 2006 ;Lou et al, 2007) reports. However, it seems now well established that we must abandon the earlier view that a single pair of parameters k off (0) and F° can fit experimental observations in all accessible situations (Alon et al, 1995 ;Fritz et al, 1998).…”
Section: How Can We Relate the Properties Of Attachments Mediated By mentioning
confidence: 99%
“…The two-pathway model with one bound state is the simplest model of the catch-slip and other 13 phenomena, and its straightforward mathematics leads to many useful analytic results. 19,20,23 One of the conceptual problems with the two-pathway model is the need for two distinct dissociation pathways that must point in opposite directions. It may be hard to visualize the two pathways, especially for such a simple bond as the disulfide.…”
Section: Introductionmentioning
confidence: 99%
“…The catch-slip binding transitions were discovered recently in a number of receptor-ligand biological complexes. 2,3,7,8,10,17,18,[21][22][23][24]26,27,32 The disulfide bond presents the first example of a chemical catch-bond, i.e., a system in which the increased lifetimes are associated with breaking a covalent bond.…”
Section: Introductionmentioning
confidence: 99%